Plasma focus as a powerful hard X-ray source for ultrafast imaging of moving metallic objects - Raspa, V. (2004)
Using high energy, pulsed X-rays, generated by a 4.7 kJ Plasma Focus operated with deuterium - argon admixtures, images of fast rotating metallic pieces were obtained. This illustrates the potential application of Plasma Focus devices for non invasive scanning of moving metallic objects. The samples for radiographic imaging were located outside the plasma focus chamber. High-sensitivity, fast-response commercial radiographic film was used as X-ray detector. The use of small doses of argon helps to enhance both the neutron production and the hard X-ray emission. By analyzing the mean attenuation of the studied radiation in different metals, an X-ray effective energy of about 100 keV was obtained.